Antimicrobial properties of copper tetraamine fluoride - Veena Wenqing Xu; Iris Xiaoxue Yin; John Yun Niu; Ollie Yiru Yu; Mohammed Zahedul Islam Nizami; Chun-Hung Chu (Journal of Applied Biomaterials & Functional Materials)
Background: A stable copper tetraamine fluoride (CTF) with low cytotoxicity has been developed for dental use. Objective: To investigate the antimicrobial effects of CTF against common microbes associated with dental caries and periodontal disease. Method: The minimum inhibitory concentrations (MIC) and minimum bactericidal/fungicidal concentrations (MBC/MFC) were used to evaluate the antimicrobial effects of CTF against eight common bacteria and one fungus associated with dental caries and periodontal disease. These nine microbes included cariogenic pathogens ( Streptococcus mutans , Streptococcus sobrinus , Lactobacillus acidophilus , Lacticaseibacillus casei , Actinomyces naeslundii and Candida albicans ), pulpitis-related bacteria ( Enterococcus faecalis ) and periodontal disease-related bacteria ( Porphyromonas gingivalis and Actinobacillus actinomycetemcomitans ). Transmission electron microscopy (TEM) was employed to examine the morphological changes of microbes with and without CTF treatment. Results: The MIC of CTF against nine microbes ranged from 80 ppm ( Lacticaseibacillus casei ) to 640 ppm ( Candida albicans and Enterococcus faecalis ). The MBC/MFC ranged from 320 ppm ( Lacticaseibacillus casei ) to 2560 ppm ( Candida albicans ). TEM revealed abnormal curvature of cell membranes, disrupted cell membranes, cytoplasmic clear zone, and cytoplasmic content leakage of the microbes treated with CTF. Conclusion: CTF has antimicrobial effects against common oral pathogens and presents a promising antimicrobial agent to aid management of dental caries and periodontal disease.